AW(k)-type Salkowski Curves in Euclidean 3-Space IE^3 - İlim Kişi (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
We deal with AW(k)-type Salkowski(anti-Salkowski) curves with constant in the Euclidean3-space. We show that there is no AW(1)-type Salkowski curve and AW(1)-typeanti-Salkowski curve in . Also, we handle weak AW(2)-type and weak AW(3)-typeSalkowski (anti-Salkowski) curves. Also, we show that there is no weak AW(2)-typeSalkowski curve in .